2022
DOI: 10.1080/21505594.2022.2069325
|View full text |Cite
|
Sign up to set email alerts
|

An iron-chelating sulfonamide identified from Drosophila-based screening for antipathogenic discovery

Abstract: We exploited bacterial infection assays using the fruit fly Drosophila melanogaster to identify anti-infective compounds that abrogate the pathological consequences in the infected hosts. Here, we demonstrated that a pyridine-3- N -sulfonylpiperidine derivative ( 4a ) protects Drosophila from the acute infections caused by bacterial pathogens including Pseudomonas aeruginosa . 4a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The ability of Pcc21 strains to colonize the insect gut was assessed using the fruit fly, Drosophila melanogaster strain Oregon R. Flies were grown and maintained at 25 °C using corn meal‐dextrose medium (6.24% yeast extract, 4.08% corn meal, 8.62% dextrose, 0.1% methyl paraben, 0.45% (v/v) propionic acid, and 0.93% agar) as previously described 43 . At least 40 flies were starved for 4 h and fed on corn meal‐dextrose medium overlaid with each Pcc21 strain (1 × 10 7 CFU) for 16 h, which had been grown to the early stationary growth phase (OD 600 of ~1.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of Pcc21 strains to colonize the insect gut was assessed using the fruit fly, Drosophila melanogaster strain Oregon R. Flies were grown and maintained at 25 °C using corn meal‐dextrose medium (6.24% yeast extract, 4.08% corn meal, 8.62% dextrose, 0.1% methyl paraben, 0.45% (v/v) propionic acid, and 0.93% agar) as previously described 43 . At least 40 flies were starved for 4 h and fed on corn meal‐dextrose medium overlaid with each Pcc21 strain (1 × 10 7 CFU) for 16 h, which had been grown to the early stationary growth phase (OD 600 of ~1.0).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of Pcc21 strains to colonize the insect gut was assessed using the fruit fly, Drosophila melanogaster strain Oregon R. Flies were grown and maintained at 25 °C using corn meal-dextrose medium (6.24% yeast extract, 4.08% corn meal, 8.62% dextrose, 0.1% methyl paraben, 0.45% (v/v) propionic acid, and 0.93% agar) as previously described. 43 At least 40 flies were starved for 4 h and fed on corn meal-dextrose medium overlaid with each Pcc21 strain (1 × 10 7 CFU) for 16 h, which had been grown to the early stationary growth phase (OD 600 of ∼1.0). At the designated time points (0.5, 2, 4, 6, 8, 10, 12, and 24 h), the intestines of five flies were homogenized with a tissue homogenizer (Yamato Scientific Co., Ltd., Tokyo, Japan) in PBS buffer (1 mL) and plated onto LB plates containing antibiotics, which were incubated at 30 °C for 24 h. Rifampicin (50 μg/mL) and kanamycin (50 μg/mL) were used for Pcc21 wild-type and the mutant, respectively.…”
Section: Bacterial Colonization In the Insect Gut Assaymentioning
confidence: 99%
“…Along the same line, the iron chelators tropolone (TRO), clioquinol (CLI), ciclopirox olamine (CO), and doxycycline (DOXY) increase the effectiveness of the peptidic antibiotic thiostrepton against P. aeruginosa and other bacterial pathogens (Chan et al, 2020). Recently, a sulfonamide that attenuates P. aeruginosa virulence thanks to its iron-chelating activity has been identified (Yoo et al, 2022). These recent findings support that prevention of iron acquisition is a potent novel approach to treat P. aeruginosa infections.…”
Section: Utilization Of Iron Chelators To Diminish the Amount Of Circ...mentioning
confidence: 99%
“…Iron is a trace element that is required for normal bacterial growth and development. Numerous studies have shown that bacterial biofilm formation is significantly inhibited under iron deficiency conditions. In addition, pyocyanin inhibition can be accelerated by iron chelators that alter iron availability in the culture media . The 3-hydroxypyridin-4­(1 H )-one structure of compound 16e and natural quorum sensing signaling molecule PQS has been reported to be a special iron chelating scaffold, and its structural derivative, deferiprone, is a clinically approved iron chelating agent .…”
Section: Biological Evaluationmentioning
confidence: 99%
“…40−43 In addition, pyocyanin inhibition can be accelerated by iron chelators that alter iron availability in the culture media. 44 The 3-hydroxypyridin-4(1H)-one structure of compound 16e and natural quorum sensing signaling molecule PQS has been reported to be a special iron chelating scaffold, and its structural derivative, deferiprone, is a clinically approved iron chelating agent. 45 Therefore, we also evaluated the iron chelating ability of compound 16e.…”
Section: Effects Of Compound 16e On Siderophoresmentioning
confidence: 99%